Effect of diet form and feeder adjustment on growth performance of nursery pigs - Nemechek, J.E.; Fruge, E.; Hansen, E.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to determine the effect of feeder adjustment and diet form on growth performance of nursery pigs. In Exp. 1, a total of 210 nursery pigs (PIC 1050 × 327, initially 26.2 lb BW) were used in a 21-d trial. In Exp. 2, a total of 1,005 nursery pigs (Fast × PIC sows × TR4 boars, initially 31.1 lb BW) were used in a 28-d trial. Treatments in both experiments were arranged as 2 × 3 factorials with main effects of feeder adjustment and diet form. The 2 feeder adjustments consisted of a narrow feeder adjustment (minimum gap opening of 0.50 in.) and a wide adjustment (minimum gap opening of 1.00 in.). The feeders were adjusted to the minimum gap setting, but the agitation plate could be moved upward to a maximum gap opening of 0.75 or 1.25 in, respectively. The 3 diet forms were meal, poor-quality pellets (70% pellets and 30% fines), and screened pellets with minimal fines. Pigs were weighed weekly to calculate ADG, ADFI, and F/G.
Keywords: Swine; Diet form; Feeder adjustment; Pellet; Nursery pig